Transcendence : healing and transformation through transcendental meditation - Rosenthal, Norman E. (New York : Jeremy P. Tarcher/Penguin, 2011)
Rosenthal describesTranscendental Meditation, the technique taught by Maharishi Mahesh Yogi, who developed it from his Indian spiritual tradition. TM is practiced by using an individual silent mantra to focus and relax, and Rosenthal shows the long-term benefits of this practice.
Includes bibliographical references and index.
Keywords: Transcendental Meditation; Meditation